Head first : the biology of hope - Cousins, Norman (New York : Dutton, 1989)
Presents the scientific evidence that hope, faith, love, will to live, and festivity can help combat serious disease.
Includes bibliographical references (p. 349-352).
Adult
Adult
Wilson's Public Library
Booklist
Library Journal Starred
Keywords: Emotions -- Health aspects; Mind and body; Medicine and psychology; Psychosomatic medicine